Mechanical loading prevents bone destruction and exerts anti-tumor effects in the MOPC315.BM.Luc model of myeloma bone disease. (1st January 2021) - Rummler, Maximilian; Ziouti, Fani; Bouchard, Alice L.; Brandl, Andreas; Duda, Georg N.; Bogen, Bjarne; Beilhack, Andreas; Lynch, Maureen E.; Jundt, Franziska; Willie, Bettina M.
Abstract: Bone continually adapts to changing external loading conditions via (re)modeling (modeling and remodeling) processes. While physical activity is known to beneficially enhance bone mass in healthy individuals, little is known in how physical stimuli affect osteolytic bone destruction in patients suffering from multiple myeloma bone disease. Multiple myeloma (MM) is caused by malignant plasma cells in the bone marrow, shifting the balance in bone remodeling towards massive resorption. We hypothesized that in vivo tibial mechanical loading has anabolic effects in mice with locally injected MOPC315.BM.Luc cells. Conventional microCT analysis revealed enhanced cortical bone mass and microstructure in loaded compared to nonloaded mice. State-of-the-art time-lapse microCT based image analysis demonstrated bone (re)modeling processes at the endosteal and periosteal surfaces as the underlying causes of increased bone mass. Loading prevented the progression and development of osteolytic destruction. Physical stimuli also diminished local MM cell growth and dissemination evidenced by quantification of MM cell-specific immunoglobulin A levels in the serum of mice and by bioluminescence analysis. These data indicate that mechanical loading not only rescues the bone phenotype, but also exerts cell-extrinsic anti-myeloma effects in the MOPC315.BM.Luc model. In conclusion, the use of physical stimuli should be further investigated as an anabolic treatment for osteolytic bone destruction in patients with MM. Graphical abstract: